Influence of dislocation density of nickel on dissolution kinetics in acidic chloride electrolyte - Alexey D Vasilyev (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2014)
An inﬂuence of dislocation density of nickel’s anode on the density of anode current and the homogeneity of anode's dissolution along the surface in the acidic chloride electrolyte was studied. To create the dislocation density of about 109 cm -2, nickel was annealed at the temperature of 900 °С for 0.5 hour. To raise the dislocation density up to 1010 cm -2, nickel was deformed by 15 % through forging. It was detected that an increase of dislocation density of one order of magnitude enlarged the density of anode current by several times over. An electrochemical etching of annealed nickel was occurring fairly even along the surface of sample revealing the well-formed grain structure. Dissolution of deformed nickel was uneven along the surface, and the grain structure was not discovered.